Analisis Faktor-Faktor Yang Mempengaruhi Willingness To Subscribe: Telaah Pada Layanan Video On Demand Netflix - Venni Ariestya Hasan (Ultima Management : Jurnal Ilmu Manajemen, 2017)
The present study is to identified factors that affecting the willingness of subscribe of video streaming services which is Netflix. The conceptual framework for this study included two antecedents of behavioral intention as proposed by TAM which are Perceived ease of use and Perceived usefulness. On other hand, four first order construct interactivity, perceived price, content richness, and free alternative was added to the framework. Theoretical model in this study are presented with 6 hypotheses to be tested with structural equation model. Sampe data was collected using questionnaire method from 140 respondents who are aware of Netflix and already tried the free trial offer from Netflix. The result derived from fitting the SEM on the sample indicated that Willingness to subscribe is positively influenced by Content Richness, Perceived Usefulness, perceived ease of use, but negatively influenced by Free Alternatives and Perceived price. On the other hand, result shows no significant effect between Interactivity and Willingness to Subscribe Keywords: Video streaming, Perceived ease of use, Perceived usefulness, Content Richness, Willingness to Subscribe